Ryanodine-induced structural alterations in the RyR channel suggested by neomycin block. - Mead, Fiona (2002)
In Mead and Williams, (Biophys. J. 82:1953-1963, 2002) we have reported that neomycin is a potent partial blocker of single purified sheep cardiac SR calcium release channels. Neomycin is unusual in that it is capable of blocking when applied to either the cytosolic or the luminal face of the channel. Block at either aspect of the channel is both concentration- and voltage-dependent, but exhibits different blocking parameters. In this study we have investigated the actions of neomycin on ion handling in the ryanodine-modified channel. Neomycin is more effective at the cytosolic face, having a Kb(0) value of 534.9 +/- 35.17 nM compared with a Kb(0) value of 971.5 +/- 66.62 nM for the luminal face. The voltage dependence also differs at the two sites. Values of zdelta for cytosolic and luminal neomycin are 1.09 +/- 0.04 and -0.57 +/- 0.03, respectively. The interaction of neomycin with the ryanodine-modified channel differs notably from that in the unmodified channel. Voltage-dependent relief of block is not observed after ryanodine modification, and the luminal blocking characteristics are altered. This suggests that ryanodine induces changes at the luminal mouth of the channel and may confer increased rigidity to the channel protein.